Targeted nanocarriers for rheumatoid arthritis therapy: current evidence and translational barriers - Shishupal Kumar; Muneesh Kanaujaya; Pallavi Chand; Ashish Singh Chauhan; Vikash Jakhmola (Journal of Applied Pharmaceutical Research, 2026)
Background: Rheumatoid arthritis (RA) remains a debilitating autoimmune disorder characterized by chronic synovial inflammation and progressive joint destruction. Conventional systemic therapies provide symptomatic relief but often fail to achieve site-specific delivery, leading to adverse effects and limited long-term efficacy. This review appraises the available evidence for the use of targeted nanocarrier drug delivery systems in the treatment of RA and highlights the translational hurdles that hinder their clinical use. Methodology: A search of PubMed, Scopus, and Web of Science (2015-2025) was conducted using the keywords RA, nanocarriers, liposomes, polymeric nanoparticles, and microneedles. Result and Discussion: Liposomal and polymeric nanoparticle systems are emerging nanotechnologies that have demonstrated improved targeting and therapeutic outcomes in preclinical models. In addition, microneedle technologies show potential for less painful delivery through the skin. Conclusion: Despite encouraging results, inconsistent manufacturing reproducibility, limitations in large-scale production, and regulatory uncertainties, among others, remain factors that are slowing the transition to the clinic. Standardization of characterization procedures, validated preclinical models, and well-designed translational research are among the measures this review has identified as necessary to facilitate the transition of nanocarrier-based therapeutics to clinical application in RA.